Paget’s Disease and Secondary Hyperparathyroidism: Is Healing Possible? - Panuccio, Vincenzo Antonio; Tripepi, Rocco (Frontiers in Cell and Developmental Biology, 2020)
Paget bone disease (PDB) is often asymptomatic and incidentally diagnosed. It is a cause of osteoporosis and bone fragility and exposes patients to a high incidence of bone fractures. In Europe the prevalence varies according to the geographical area of origin, and increases with age. In patients with chronic renal disease, the prevalence is unknown and only few cases with PDB have been reported. We present a challenging case in an elderly patient with chronic kidney disease on peritoneal dialysis treatment. Our patients presented extremely high levels of alkaline phosphatase, suggesting a Paget bone disease. Secondary hyperparathyroidism was confirmed by the bone histological examination. The surprising biochemical and clinical response to active vitamin D confirms the well-known role on hyperparathyroidism and may indicate an additional role in the pathogenesis of Paget’s disease.